Linking aberrant chromatin features in chronic lymphocytic leukemia to transcription factor networks. Issue 5 (22nd May 2019) - Mallm, Jan‐Philipp; Iskar, Murat; Ishaque, Naveed; Klett, Lara C; Kugler, Sabrina J; Muino, Jose M; Teif, Vladimir B; Poos, Alexandra M; Großmann, Sebastian; Erdel, Fabian; Tavernari, Daniele; Koser, Sandra D; et al.
Abstract: In chronic lymphocytic leukemia (CLL), a diverse set of genetic mutations is embedded in a deregulated epigenetic landscape that drives cancerogenesis. To elucidate the role of aberrant chromatin features, we mapped DNA methylation, seven histone modifications, nucleosome positions, chromatin accessibility, binding of EBF1 and CTCF, as well as the transcriptome of B cells from CLL patients and healthy donors. A globally increased histone deacetylase activity was detected and half of the genome comprised transcriptionally downregulated partially DNA methylated domains demarcated by CTCF. CLL samples displayed a H3K4me3 redistribution and nucleosome gain at promoters as well as changes of enhancer activity and enhancer linkage to target genes. A DNA binding motif analysis identified transcription factors that gained or lost binding in CLL at sites with aberrant chromatin features. These findings were integrated into a gene regulatory enhancer containing network enriched for B‐cell receptor signaling pathway components. Our study predicts novel molecular links to targets of CLL therapies and provides a valuable resource for further studies on the epigenetic contribution to the disease. Synopsis: Transcriptome profiling and genome‐scale mapping of DNA methylation, seven histone modifications, nucleosome positions, chromatin accessibility, EBF1 and CTCF binding are performed in B cells from CLL patients and healthy donors. Altered chromatin features were detected at 80% of the differentially regulated genes in CLL and histone deacetylase activity was globally increased. Half of the CLL genome comprised partially DNA methylated domains that were transcriptionally downregulated, demarcated by CTCF and enriched for H3K9me3 and H3K27me3. H3K4me3 was redistributed at CLL promoters, including loss of bivalent H3K4me3/H3K27me3 states, and substantial changes of enhancer activity were detected. A gene regulatory network including enhancers was constructed around the transcription factors targeting 15 central binding motifs that were associated with aberrant CLL chromatin features. Genes involved in BCR signaling were enriched in the network. Abstract : Transcriptome profiling and genome‐scale mapping of DNA methylation, seven histone modifications, nucleosome positions, chromatin accessibility, EBF1 and CTCF binding are performed in B cells from CLL patients and healthy donors.